Home based formulation of personalised medicines by means of inkjet printing technique - Scoutaris, Nikolaos (2011)
The potential application of inkjet printing technology to produce precisely dosage care is demonstrated in this thesis. Inkjet printing technology as it offers the opportunity to deliver quantities with high accuracy can produce medicines tailored for each patient.